Wavelet packet transform based damage identification of GFRP beam - Prakash, R.; Sivakumar; Srinivasan, M. (Journal of Structural Engineering, 2024)
Wavelet packet transform (WPT) is a mathematical tool which is an extension of wavelet transform. This tool has been used to estimate wavelet packet energy rate index (WPERI) to indicate the structural damage in simple structures that are subjected to known input loads. In this study, a novel approach is attempted in the form of WPT being used to detect damage in a glass fiber reinforced polymer (GFRP) cantilever type beam from the response under the ambient excitation. An effectiveness of the proposed damage diagnostic tool is verified by changing the parameters such as scale, level of decomposition to identify the location and size of damage.